Risk factors for prolonged hospitalization as a marker for difficult-to-manage exacerbations of chronic obstructive lung disease (COPD): the DiMECO Study - Dorina Esendağlı; Nurdan Köktürk; Ayşe Baha; Dilek Yapar; Seçil Özkan; Elif Şen; Fatma Çiftçi; Burcu Öztürk; Sümeyye Kodalak Cengiz; Gaye Ulubay; İrem Şerifoğlu; Yelda Varol; et al. (BMC Pulmonary Medicine)
Abstract Background Exacerbation is an independent risk factor for chronic obstructive pulmonary disease (COPD)-related morbidity and mortality. Despite optimal care, there may be risk factors that lead to difficulties in managing exacerbations that may be associated with prolongation of length of hospital stay (LOS). Methods This is a multicenter prospective observational study of COPD patients hospitalized with exacerbations. Prolonged LOS was calculated according to the 50th percentile and defined as ≥ 9 days. Potentially predicting factors of LOS were stratified into 4 pillars as patient-related, disease and exacerbation-related, treatment-related and, hospital utility-related. These categories were systematically documented throughout the duration of the hospitalization. Results A total of 434 patients, 361 males and 73 females, with a mean age of 69.2 ± 9.3 years, were included in the study. Variables of each pillar were tested with univariate analysis to identify potential risk factors for prolonged LOS. Subsequently significant factors excluding factors associated with hospital utility were tested with multivariate logistic regression analysis for detecting potential associated factors for difficult-to-manage COPD exacerbation. Biomass exposure, past history of non-invasive mechanical ventilation (NIMV), low bicarbonate levels at admission, antibiotic switching, need for theophylline, increasing oxygen requirement, need for in-hospital non-invasive mechanical ventilation, nutritional support and physiotherapy were found as defining factors. Conclusions The DiMECO study can help to identify COPD exacerbators who are at risk for prolonged hospitalizations that may associate with difficult-to-manage COPD exacerbations. Difficult to manage COPD exacerbation may serve as a provocative framework, underscoring the necessity for a better understanding of the multifaceted approaches to the management of COPD exacerbations. This conceptualization warrants further investigation across diverse clinical settings to validate its applicability and efficacy.